2014
DOI: 10.1371/journal.pone.0095083
|View full text |Cite|
|
Sign up to set email alerts
|

First Evaluation of Drug-Resistant Mycobacterium tuberculosis Clinical Isolates from Congo Revealed Misdetection of Fluoroquinolone Resistance by Line Probe Assay Due to a Double Substitution T80A-A90G in GyrA

Abstract: BackgroundTuberculosis (TB) is one of the major public health problems in Congo. However, data concerning Mycobacterium tuberculosis drug resistance are lacking because of the insufficient processing capacity. So, the aim of this study was to investigate for the first time the resistance patterns and the strain lineages of a sample of M. tuberculosis complex (MTBC) isolates collected in the two main cities of Congo.MethodsOver a 9-day period, 114 smear-positive sputa isolated from 114 patients attending center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
2
24
1
1
Order By: Relevance
“…Six percent of FQ resistance, as classified by MTBDRsl, was due to the sole absence of WT probe hybridization. Our results contrast significantly with the results of two studies conducted in the Congo and the Democratic Republic of Congo, where over 60% of FQ resistance was attributable to the sole absence of WT probe hybridization (17,18). Our results more closely resemble those reported by Brossier et al (33) and Huang et al (34), in which less than 20% of FQ resistance was attributable to the sole absence of WT probe hybridization.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Six percent of FQ resistance, as classified by MTBDRsl, was due to the sole absence of WT probe hybridization. Our results contrast significantly with the results of two studies conducted in the Congo and the Democratic Republic of Congo, where over 60% of FQ resistance was attributable to the sole absence of WT probe hybridization (17,18). Our results more closely resemble those reported by Brossier et al (33) and Huang et al (34), in which less than 20% of FQ resistance was attributable to the sole absence of WT probe hybridization.…”
Section: Discussioncontrasting
confidence: 80%
“…(ii) If no MUT probes hybridize on the test strip and one or more WT probes also do not hybridize, the presence of an unknown mutation in that region is inferred, and the specimen is classified as resistant. Two recent studies assessing the performance of the MTBDRsl assay detected an unusually high proportion of FQresistant specimens that were eventually determined to be falsely positive after comparison to sequencing and/or conventional culture results (17,18). False-positive (FP) FQ resistance results from the two studies were determined to be the result of absent WT probe hybridization (interpreted to mean the presence of a nonwild-type or unknown mutation sequence) rather than direct detection of a known mutation (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that these substitutions, commonly identified in African countries such as Republic of the Congo, do not confer resistance and are thus responsible for misclassification of FQ resistance by line probe assay (23,24). This problem, already encountered with MTBDRsl v1, could be avoided by inclusion of a comment in the recommendations for interpretation of MTBDRsl v2.0 results in case of the absence of the WT2 probe.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid identification is essential to initiate early treatment, improve patient's outcomes, and more effective for public health interventions [5]. Therefore, molecular assays have been used to predict drug resistance in clinical specimens within one working day and are potentially the most rapid methods [6][7][8][9][10]. The GeneXpert MTB/RIF assay is a novel integrated diagnostic device that performs sample processing and semi-nested real-time PCR analysis in a single hands-free step for the diagnosis of tuberculosis and rapid detection of RIF resistance in clinical specimens [4,10].…”
Section: Introductionmentioning
confidence: 99%